Kepastian Hukum Pemutusan Hubungan Kerja karena Efisiensi Perusahaan Berdasarkan Undang-Undang Nomor 6 Tahun 2023 tentang Cipta Kerja - Achmad Nurwachid; Deki Satriawan; Hery Kurniawan Zaenal; Yudhistira Prawira Utama; Marco Orias (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Termination of employment (PHK) due to company efficiency poses significant legal and social challenges in Indonesia, especially after the enactment of Law Number 6 of 2023 concerning Job Creation. This study uses a normative juridical approach to analyze legal provisions, court decisions, and legal literature related to efficiency-based PHK, with a systematic and teleological interpretative framework. The results of the analysis show that although the Job Creation Law stipulates procedures and normative rights for workers through Articles 161–165, there are normative and implementative gaps that cause legal uncertainty, social conflict, and the risk of procedural injustice for workers. The socio-legal study shows that the effectiveness of legal norms depends not only on formal compliance by companies, but also on the integration of norms, practices, and the socio-economic conditions of workers. These findings emphasize the need for participatory mediation mechanisms, procedural transparency, and consistent protection of normative rights to strengthen legal certainty and social justice in the practice of efficiency-based termination. This research provides theoretical and practical contributions to the development of labor laws that are responsive to social dynamics.